Hubungan status gizi terhadap kejadian Anemia pada lansia - Ratih Delimaniar Siregar; Arneliwati - -; Fathra Annis Nauli (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2014)
The purpose of this study was to determine the relationship between nutritional status on the incidence of anemia in the elderly. This research method descriptive design-correlation with cross-sectional studies. Correlational study aimed to determine the correlation between variables. This research conducted at the health center of Pekanbaru Simpang Tiga to 40 elderly people . The sampling method is to use accidental sampling. Measuring instruments in use is the observation sheet consisting of initials, age, sex, IMT values​​, and levels of hemoglobin. Analysis used univariate and bivariate analysis is by using ANOVA test. The results of this study showed no association between nutritional status on the incidence of anemia in the elderly (p > α (0,05) is (p = 0,792). The results of this study indicate that the elderly have normal nutritional status because of lifestyle factors such as eating good nutritious food and food various every day.   Key word: anemia, elderly, nutrition, status